Relation between sexual allometry and function in the sawfly Leseha vespa (Hymenoptera Tenthredinidae). Issue 1 (2nd January 2021) - Eberhard, William G.
Abstract : A recent theoretical model predicts that the allometries of structures under sexual selection vary according to their functions in sexual interactions. Structures that are specialized for exclusive use as courtship devices, and not as weapons or threat devices, were predicted to tend to show low allometric values. Detailed observations of behavior and morphological design in Leseha vespa indicated that the sexually dimorphic abdominal tergite VIII of males functions to court females, but does not function as a weapon or in threats directed toward other males. As predicted by the theory, the allometric slope of tergite VIII length was lower than those of other body traits that were not modified for sexual interactions.